Effect of storage temperature on the chemical and microbiological properties of white cheese from Kastamonu, Turkey - Eljagmani, Salem; Altuner, Ergin Murat (Informa UK Limited, 2020)
In Turkey, white cheese is a popular choice among the consumers and comprises about 60% of the entire domestic produce. Certain cheese varieties are endemic and commercially unavailable due to socioeconomic factors. In this study, five different types of white cheese were collected from the city of Kastamonu; one as a factory-packed brand, three as local-market open products, and one produced in a farm from cow milk. The study aimed to investigate the shelf-life of the cheese samples stored at 5, 15 and 25 °C. The microbiological and chemical tests were carried out regularly on 1, 7, 14, 21 and 28 days of storage at 5, 15 and 25 °C. The shelf-lives were reportedly found to be between the days 14 and 28. The pH values were high in all cases, with no significant decrease with changes in storage duration. Conversely, the salt contents were low on day 1 and decreased during the storage at different temperatures. Microbiological examinations revealed relatively high growth of microorganisms such as coliforms, Salmonella, and Staphylococci post-storage. In addition to bacterial growth, storage at increasing temperatures also led to changes in the sensory attributes such as appearance, texture, aroma and taste of the cheese.
Keywords: S; sensory attributes; Agriculture; TP368-456; different temperatures; Food processing and manufacture; microbiological properties; white cheese; storage; shelf-life; chemical properties; 2. Zero hunger